"DELIVERY OF MEDICAL CARE BY THE HEALTH AUXILIARIES (BEHVARZ AND BEHDASHT-YAR) IN WEST-AZERBAIJAN, IRAN " - M.A.Barzgar; A.Sadeghie (Tehran University of Medical Sciences, 1978)
From 22 May 1976 to 19 February 1977 out of 27742 patients which were referred to health and social welfare network of west Azerbaijan in Chonqralu (Field laboratory of school of public health and institute of public health research in health services development research project in Iran), 22693 (81.81%) simple cases were managed by the Behvarz (Female front line health worker), in nine health houses, and 5049 cases or 18.19% were referred to the physician in Chonqralu rural health center were referred to the hospital or specialized health centers. So with establishing of this kind of health and welfare network (using of health auxiliary worker) we will be able first to make primary health care services accessible and available to most of the people of the country especially in rural area, and secondly to decrease the load of health services system.